Pengambilan Keputusan Menentukan Jurusan Kuliah Ditinjau Dari Student Self Efficacy Dan Persepsi Terhadap Harapan Orang Tua - Wisnu Prabowo; Munawir Yusuf; Rini Setyowati (Program Studi bimbingan Konseling PPs UNM Makassar, 2019)
This study aims to determine the relationship between student self efficacy and perceptions of parents' expectations with decision making in determining the college majors. The research sampling used cluster random sampling of 147 students from 5 classes. The research instrument used the scale of decision making to determine the majors (r = 0.868), student self efficacy scale (r = 0.858), and the scale of perceptions of parents' expectations (r = 0.888). The data analysis technique of this study used multiple linear regression. Based on multiple linear regression test, the value of Fcount = 39.116> Ftable = 3.06 (p = 0.000 <0.05) with a value of R = 0.593. The total contribution of student self efficacy and perceptions of parents' expectations for decision making determines the course major of 0.352. Based on the partial test, it showed that there are a relationship between student self-efficacy and decision making in determining the majors (p = 0.43 <0.05 rx1y = 0.140) and there are a relationship between perceptions of parents' expectations and decision making in determining the majors (p = 0,000 <0,05; rx2y = 0,549). This study concluded that there are a significant positive relationship between student self efficacy and perceptions of parents' expectations with decision making in determining the college majors in high school students.